Antibiotic Resistance and Serotypes Distribution in Streptococcus agalactiae Bulgarian Clinical Isolates During the Years of 2021–2024 - Boyanov Vasil S.; Alexandrova Alexandra S.; Hristova Preslava M.; Hitkova Hristina Y.; Gergova Raina T. (Polish Journal of Microbiology)
Streptococcus agalactiae (group B Streptococcus, GBS) is an important human and animal pathogen. In recent years, the number of streptococcal isolates resistant to antimicrobial agents has increased in many parts of the world. Various mechanisms of antimicrobial resistance and capsular serotypes of GBS with different geographical distributions can be found. A prospective cross-sectional study was conducted from September 2021 to May 2024. The survey included 257 GBS isolates from Bulgarian inpatients and outpatients with streptococcal infections. Antibiotic resistance genes and capsular serotypes were detected and evaluated using polymerase chain reaction (PCR). We classified GBS isolates into groups according to their source as vaginal samples (191) and extra-vaginal samples (66), subdivided as invasive (36) and non-invasive specimens (30). The most common serotypes were Ia (26.5%), III (20.2%), and V (19.8%). Antimicrobial susceptibility testing revealed that all examined isolates were susceptible to penicillin and vancomycin. Resistance to macrolides, lincosamides, and tetracyclines was observed in 60.3%, 24.9%, and 89.1% of the isolates. The distribution of phenotypes was cMLSb 47.4%, iMLSb 30.8%, M-type 21.2%, and L-type 0.6%. PCR analysis revealed nine genes associated with macrolide and lincosamide resistance: ermB (54.2%), ermA/TR (30.3%), mefA (20.7%), ermC (18.1%), msrD (14.8%), mefE (8.4%), IsaC (8.4%), InuB (7.7%), and IsaE (6.5%). Two genes linked to tetracycline resistance tetM (89.1%) and tetO (14.4%) were detected. Compared to the previous period, we observed increased antibiotic resistance. There was no statistical significance between the distribution of serotypes and antimicrobial non-susceptibility depending on the sample source.